On some fractional order hardy inequalities - Kufner Alois; Persson Lars-Erik; Heinig Hans P (Journal of Inequalities and Applications, 1997)
Weighted inequalities for fractional derivatives ( fractional order Hardy-type inequalities) have recently been proved in [4] and [1]. In this paper, new inequalities of this type are proved and applied. In particular, the general mixed norm case and a general twodimensional weight are considered. Moreover, an Orlicz norm version and a multidimensional fractional order Hardy inequality are proved. The connections to related results are pointed out.